Sell-side analysts and mutual fund managers: Complements or substitutes? - Park, Haerang; Oh, Byungmin (Journal of Banking & Finance, 2025)
We examine whether analyst coverage and mutual fund trades are complements or substitutes in the course of information incorporation into stock prices. Our empirical evidence indicates that they are complementary. Clustered trades in stocks with low analyst coverage is associated with a subsequent return reversal, which is more pronounced among less actively managed mutual funds. Mutual fund herding under low analyst coverage also amplifies future stock price crash risk through decreased corporate disclosure quality. These negative effects of mutual fund herding are not apparent for stocks with high analyst coverage. To address potential endogeneity concerns, we conduct additional tests using brokerage firm mergers and closures as exogenous shocks to analyst coverage and find consistent results. Our findings highlight the role of analysts in mitigating price-destabilizing herding behavior of mutual funds.